Health beliefs and willingness to engage in T2D preventive behaviours among Malay youth: a qualitative inquiry - Mohd. Asraf, Ratnawati; Hanah, Atiqah; Supian, Nadya (Kulliyyah of Education, International Islamic University Malaysia, 2022)
Due to sedentariness and poor diet and nutrition, the youth of today are increasingly exposed to early-onset Type 2 diabetes (T2D). Malaysian youth are particularly at risk for T2D since Malaysia has the highest prevalence of obesity among its young population in Asia. Our concern led us to the conduct of this study, which was aimed at discovering what sixteen young Malaysian undergraduates knew about T2D, their health beliefs, and their perspectives on T2D and lifestyles. The study also sought to ascertain if the youth would be willing to engage in T2D prevention behaviours to ward off the onset of the disease. The results of the study would help to inform us of the beliefs that other Malaysian youth may have on this issue and also of the possible content that we could propose for Diabetes Awareness Programmes aimed at Malaysian youth. The interview questions were based on the six constructs of the Health Belief Model (Abraham & Sheeran, 2014) and a written interview was conducted via email with the 16 undergraduates. The data, analysed thematically, produced seven themes. We found that the participants generally lacked proper knowledge of and are confused between types of diabetes. Nonetheless, they expressed a willingness to alter their lifestyles to incorporate healthier habits and a more nutritional diet, but were deterred by family attitude, social norms, and social media influence. We recommend two urgent actions. First, an awareness programme to enhance youth’s knowledge of T2D to showcase its gravity and consequences. Second, educating the public, especially families, on rendering support to youth who wish to live a healthier, diabetes- free life.